Managed competition in the Netherlands: Do insurers have incentives to steer on quality?. Issue 3 (March 2019) - Stolper, Karel C.F.; Boonen, Lieke H.H.M.; Schut, Frederik T.; Varkevisser, Marco
Highlights: Managed competition offers insurers ambiguous incentives to steer on quality. Insurers are caught in a struggle between positive and negative incentives. CEOs perceive more positive incentives than purchasers and marketers. Social mission is an important but vulnerable incentive in a competitive market. Better quality information is key to foster insurers' ability and legitimacy to steer on quality. Abstract: In health care systems based on managed competition, insurers are expected to negotiate with providers about price, quantity, and quality of care. The Dutch experience shows that this expectation may be justified with regard to price and quantity, but for quality the results are less conclusive. To examine the incentives insurers face for enhancing quality of care, we conducted in-depth interviews with CEOs and organised separate focus groups with purchasers and marketers of five Dutch health insurers. Jointly these insurers account for more than 90 percent of the market. We distinguished three categories of both positive and negative incentives to steer on quality: social, competitive and financial incentives. The overall picture emerging is that insurers are caught in a struggle between positive and negative incentives, with CEOs being more positive about the incentives to steer on quality than purchasers and marketers. At present, the social mission perceived by insurers seems to be their most important driver to invest in quality enhancement. However, whether or not the role of the social mission is sustainable in a competitive market remains unclear. Improving publicly available information on quality therefore seems to be crucially important for reinforcing the positive as well as counteracting the negative incentives insurers face with respect to enhancing quality of care.